VALIDITY AND RELIABILITY OF PERFORMANCE ASSESSMENT OF ACETIC ACID VISUAL INSPECTION - Tri Hariyati; Zulpan Zulpan (Jurnal Literasiologi, 2018)
An assessment of performance that has a high level of validity and reliability is needed, because the assessment technique is said to be valid or whether the assessment can be influenced by the instrument. This study aims to develop performance evaluations for midwifery students in valid and reliable of acetic acid visual inspection. Instrument development refers to the Djemari Mardapi development research model with nine steps of development. The technique of collecting data by interview and observation. The results of content validity show that 21 items have a value of> 0.3, the results of reliability based on expert agreement show a value of 0.82 which means that experts agree in assessing. The results of KMO in the field test obtained values ??of 0.904 MSA> 0.5, and Bartlett's test significance was 0,000 so that the instrument items could be analyzed further. There are five factors formed from 21 items available, each item in each factor has a value of loading factor> 0.3 then for Alpha Cronbach's coefficient the value is 0.878. The results of this study can be used as a reference for making an assessment of the performance of students in midwifery practices in the institution.